What makes an entrepreneur and does it pay? Native men, Turks, and other migrants in Germany - Klaus F. Zimmermann; Yochanan Shachmurove; Amelie F. Constant (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper focuses on the entrepreneurial endeavors of immigrants and natives in Germany. We pay closer attention to Turks, since they are the largest immigrant group with a strong entrepreneurial tradition, and the self-employed Turks in Germany represent about 70% of all Turkish entrepreneurs in the European Union. We identify the characteristics of the self-employed individuals and understand their underlying drive into selfemployment. At the same time we investigate how immigrant entrepreneurs fare in the labor market compared to natives. Employing data from the German Socioeconomic Panel 2000 release we find that the probability of self-employment increases significantly with age for all groups albeit at a decreasing rate. Among immigrants, Turks are twice as likely to choose self-employment as any other immigrant group. The age-earnings profiles of self-employed German and immigrant men are concave and surprisingly similarly shaped. While for self-employed German men hours of work and Treiman prestige scale scores increase their earnings, for self-employed immigrant men it is the longevity of the business that makes a difference. Everything else equal, the earnings of self-employed Turks are no different from the earnings of the self-employed Greeks, Italians, Spaniards, ex- Yugoslavs, Polish or other East Europeans, including those immigrants who have become German citizens.
Keywords: J23; M13; J24; J61; J31; 330; Entrepreneurship; self-employment; occupational choice; immigrants; wage differentials; Unternehmer; Selbständige; Migranten; Türken; Lohnstruktur; Schätzung; Deutschland